DIGITALIZING LITERATURE AND DIGITAL LITERATURE (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
This study aims to examine the transformation of literature driven by the communication and production methods of the digital age, and to clarify the critical distinction between the two main concepts that emerge during this process: “digitalizing literature” (or digitized literature) and “digital literature”. By addressing the historical evolution of human narrative efforts from written communication to the printing press, and subsequently to the digital environment, the paper investigates how digitalization influences literature. In contrast, digital literature (electronic literature) consists of works that necessarily require digital technology and computation to exist. These types of works are digital-born and contain elements (multimedia, animation, hyper-textual structures that change based on reader input) that would have no meaning on paper. Coding, in this context, is an inseparable part of the work's aesthetic and artistic expression. The correct determination of the distinction between these two concepts carries an essential value for the establishment of a sound theoretical framework for both literary studies and communication studies in the digitalizing world.
Keywords: Digital literature; Digitalizing literature; Electronic literature; Digital transformation; Interaction; Hypertext; Literature.